2017
DOI: 10.1021/jacs.6b12976
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Framework Enhances Electronic Communication of Ultrasmall-Sized Nanoparticles for Exceptional Solar Hydrogen Evolution

Abstract: Colloidal quantum dots (QDs) have demonstrated great promise in artificial photosynthesis. However, the ultrasmall size hinders its controllable and effective interaction with cocatalysts. To improve the poor interparticle electronic communication between free QD and cocatalyst, we design here a self-assembled architecture of nanoparticles, QDs and Pt nanoparticles, simply jointed together by molecular polyacrylate to greatly enhance the rate and efficiency of interfacial electron transfer (ET). The enhanced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
97
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 156 publications
(101 citation statements)
references
References 68 publications
4
97
0
Order By: Relevance
“…Aproof-of-concept model consisting of multiple QDs and as ingle cocatalyst has been established for advanced photocatalytic H 2 evolution in the presence of sacrificial reagent (Figure 5b,inset). [39] In this flexible assembly,CdSe/CdS QDs and Pt nanoparticles were joined together via molecular polyacrylate.P tn anoparticles were chosen as the cocatalysts for their outstanding proton reduction and multi-electron storage properties. [40] Femtosecond transient absorption spec-troscopy showed that the interparticle electron transfer from QDs to Pt nanoparticle occurred on at ime scale of approximately 65 ps.F urthermore,t he kinetics of ultra-fast and consecutive electron transfer from CdSe/CdS QDs to Pt nanoparticles was studied by X-ray transient absorption spectroscopy for the first time.T he difference X-ray absorption near edge structure spectra of the Pt L 3 absorption edge obtained at adelay time of 60 ps showed the partial reduction of Pt atoms,d irectly manifesting the capture of photoelectrons from QDs.C orrespondingly,t he discharge kinetics of electrons at the Pt nanoparticle/electrolyte interface was much slower (> 2ns).…”
Section: Electrostatic Interaction Induced Qd Assemblymentioning
confidence: 99%
“…Aproof-of-concept model consisting of multiple QDs and as ingle cocatalyst has been established for advanced photocatalytic H 2 evolution in the presence of sacrificial reagent (Figure 5b,inset). [39] In this flexible assembly,CdSe/CdS QDs and Pt nanoparticles were joined together via molecular polyacrylate.P tn anoparticles were chosen as the cocatalysts for their outstanding proton reduction and multi-electron storage properties. [40] Femtosecond transient absorption spec-troscopy showed that the interparticle electron transfer from QDs to Pt nanoparticle occurred on at ime scale of approximately 65 ps.F urthermore,t he kinetics of ultra-fast and consecutive electron transfer from CdSe/CdS QDs to Pt nanoparticles was studied by X-ray transient absorption spectroscopy for the first time.T he difference X-ray absorption near edge structure spectra of the Pt L 3 absorption edge obtained at adelay time of 60 ps showed the partial reduction of Pt atoms,d irectly manifesting the capture of photoelectrons from QDs.C orrespondingly,t he discharge kinetics of electrons at the Pt nanoparticle/electrolyte interface was much slower (> 2ns).…”
Section: Electrostatic Interaction Induced Qd Assemblymentioning
confidence: 99%
“…In this case, unfortunately, the loading of cocatalyst on a single‐molecule catalyst is relatively difficult due to the limited interface contact area . As a result, the diffusion‐controlled bimolecular electron transfer process between the individually separated small‐molecule catalyst and cocatalyst becomes the bottleneck to achieve high photocatalytic efficiency …”
Section: Introductionmentioning
confidence: 99%
“…Then, the electron-hole recombination is drastically suppressed. [18] In addition, another evidencef or the acceleration of charget ransport is summarized from EIS analysis ( Figure 2d). Ni 3 P/Ni/CdS shows am uch smallers emicircle in the middle-frequency region, compared with that of pure CdS NRs, which could result from its fast interfacial electrons transfer between the photocatalyst and the scavenger.O verall,t hose results verify that metallic Ni 3 P/Ni co-catalyst could effectively trap electrons, and lead to the enhancement of charget ransfer process and the suppression of electron-hole pair recombination.…”
mentioning
confidence: 99%